Theo Altmaier: capstone - Altmaier, Theo, artist (Colorado State University. Libraries, 2024)
The artist's statement: Painting is an instinctive way for me to express my inner world. Right now, my inner world contains a lot of grappling with religion and esoteric topics. As a neurodivergent person, I find traditional modes of communication – both written and spoken – challenging so I paint. It feels like the only way I can "talk" comfortably. I think of what I do (painting) as an act of translation instead of creation. I translate my experiences and thoughts into a perceivable medium. I work with oil paint on metal and canvas surfaces. Tarot, the occult, Paganism, and religious archetypes have played a major role in inspiring my art. My current body of work focuses on surreal figures and landscapes as a vessel to process my ideas about the divine and what I see in the world. I do not aim to make sense or develop a final answer about any of the topics I am painting about. I am one artist in an infinite lineage of religious scholars, philosophers, priests, priestesses, and other artists who all have something to say (and some claim to even have The Answers) about the divine. I do not and will not have answers. All I have is paint, surface, and time.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting